CORONAVIRUS SARS-COV2 and COVID-19: The World in Stand By - Gómez-Meléndez, Agustín (2022)
SARS-CoV2 and its disease COVID-19 have provoked more than 6 billion infections and nearly 6 million registered deaths since the first diagnosed case in Wuhan, China. It is considered the first pandemic that the modern world has faced that was able to ground all air services and contain all families in their homes. The high contagion capacity of the virus associated with its high lethality in people with risk factors placed the world economy in a close balance between economic aspects and public and individual health. The economic, material, and human losses increased the current social gaps. Then, a reflection of the main events that have occurred from 2019 to date and the impact caused by COVID-19 in the world is presented. The economic recession is considered as part of the results, besides the shipping-container crisis, and the implemented health measures and their effects. The article concludes with four lessons on epidemiological intelligence, resilience, the ability to learn to plan for the future, and the correct risk management.